Konsep Manajemen Pemasaran dalam Peningkatan Citra Lembaga Pendidikan - Ahmad Shiroth; Diningrum Citraningsih (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
The number of schools in Indonesia is increasing year by year. Competitive competition between educational institutions is unavoidable and needs to be responded to appropriately. This complicated problem coupled with the relatively low quality of management of Islamic education institutions can be a threat to the existence of Islamic educational institutions. This research was conducted with the aim of knowing the marketing management system and the efforts that can be made by Islamic educational institutions to improve the image of Islamic educational institutions. The method used in this research is a descriptive-qualitative research method that emphasizes library research using secondary data in the form of books and previous scientific articles that are relevant to the research topic. The results of this study indicate that educational marketing management can be interpreted as managerial activities of educational institutions carried out in order to create, maintain and enhance profitable exchange interactions with other parties to achieve the goals of the institution. In its application, educational marketing management applies marketing management concepts, including marketing planning, marketing organizing, marketing actuating and marketing controlling. Efforts to maintain and enhance the positive image of Islamic institutions are (1) Applying Islamic principles in marketing in service, appearance, persuasion and satisfaction. mproving the quality of Islamic education services through improving the quality of human resources. (3) Digitalizing of marketing of Islamic education services by utilizing technological developments for the branding of Islamic educational institutions